Spectral light quality regulates photosynthesis and thylakoidal protein complexes to improve drought tolerance in okra rootstocks - Suresh, Preethika; Rameshkumar, Srinivasan; Lee, Kyung Hee; Bae, Dong Won; Muneer, Sowbiya (Frontiers in Plant Science, 2026)
IntroductionGlobal agriculture is seriously threatened by drought stress, especially in arid and semi-arid areas where crop production is already low. Okra (Abelmoschus esculentus L.), a nutritionally beneficial yet underutilized crop, experiences considerable productivity and quality losses. Plant cellular activities are modulated by light quality, which impacts stress adaptation. To increase okra productivity and stress resilience, this study attempts to optimize the performance of drought-resilient rootstocks under various spectral light conditions.MethodsTwo okra genotypes, NS 7772 and NS 7774, were evaluated in this study under drought conditions with two light spectra: red: blue: white (R: B) light-emitting diodes (LEDs) and white light (WL).Results and discussionInfrared thermographic images showed lower canopy temperatures, indicating increased water content under R:B light conditions. NS-7774 exhibited improved drought tolerance confirmed by decreased malondialdehyde (MDA) levels and enhanced antioxidant enzyme activity. Metabolic stability was indicated by preserved photosynthetic protein complexes and stress-responsive polypeptides in the thylakoidal multiprotein complex profiling. Nutrient preservation was validated through SEM-EDAX analysis, assessments of chlorophyll, total soluble protein, isoenzyme patterns, and antioxidant activity (CAT, SOD, APX, GPOX). Multivariate analysis highlighted six critical factors contributing to resilience. These results demonstrate that combinational spectral light modifications can greatly increase the tolerance of okra to drought. The superior performance of NS 7774 under R:B light conditions suggests the potential suitability of NS 7774 for cultivation in drought-prone zones of India.